Collaborative work in the performance of the panpipes in university students in times of semi-presenciality - Olga Mendoza-León; Iris Liliana Vasquez Alburqueque; Yoya Betzabé Flores Pérez; Joselito Moisés Luján Miguel; Wilson Hugo Chunga Amaya; José Wualter Peláez Amado (Institute of Advanced Engineering and Science, 2025)
In the context of blended learning and music education, difficulties were identified in the learning of traditional instruments, such as the panpipes, due to the absence of collaborative methodologies that encourage teamwork. This study was conducted with the objective of improving the performance of the panpipes in university students through collaborative learning, promoting a positive attitude towards cooperation and a constant feedback process. The research included the participation of 46 students and was developed under a qualitative approach, using the action research method. For data collection, techniques such as participant observation, discourse analysis, taking photographs and grounded theory were used. The findings showed significant discursive patterns and revealed students’ perceptions and interactions during the process. The implementation of collaborative strategies fostered active participation, negotiation, and joint construction of musical knowledge, while continuous feedback improved both students’ attitudes toward learning the panpipes and their musical performance. In conclusion, collaborative learning was shown to be an essential methodology for more effective music teaching.